The importance of having self-efficacy, self-esteem, job satisfaction on employee performance during the pandemic in state-owned companies - Ilham Wicaksono; Intan Ratnawati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
Employee performance is a study that has received wide attention. Performance-forming factors are found with various variations that continue to grow. In the setting of the Covid-19 pandemic, employee performance is examined as part of how workers deal with different work conditions. This paper aimed to investigate the effect of self-efficacy and self-esteem on employee performance by using job satisfaction as an intervening variable. This study uses a quantitative approach with Structural Equation Model (SEM) analysis techniques to test the model and provide an evaluation of prior related research. AMOS is used as data processing software. Data were collected from 160 Generation X employees of PT. PLN Persero DIY and Central Java Distribution Area. The results were then analyzed using the SEM technique. As hypothesized, self-esteem and self-efficacy proved to, directly and indirectly, affect the employees' job satisfaction and work performance. This study provides scientific facts that employee performance models can be built on a cause-and-effect relationship with the variables of self-efficacy, self-esteem, and job satisfaction. The findings of this study also have a managerial impact on the management of employees within the State-Owned Enterprises. Originality – The COVID-19 outbreak has changed for generation X. However, how the internal factors affect the work performance in Generation X has not been well understood. Thus, the research aimed to explore those interactions.